New Degree-Based Topological Indices of Toroidal Polyhex Graph by Means of M-Polynomial - Farkhanda Afzal; Mohammad Zeeshan; Deeba Afzal; Sufian Munawar; Dhan Kumari Thapa; Alina Mirza (Journal of Mathematics)
Graph theory is the principal field of mathematics. In this manuscript, we have discussed the toroidal polyhex graph. Some new indices such as reduced reciprocal randic, arithmetic geometric, SK, SK1, SK2 indices, First Zagrab, the general sum-connectivity, SCIλ, and the forgotten index have been used. We have computed the closed form of topological indices of toroidal polyhex graph via M-Polynomial.